Rural health enterprises in the EU context: a systematic literature review and research agenda. Issue 4 (14th June 2020) - Apostolopoulos, Nikolaos; Ratten, Vanessa; Stavroyiannis, Stavros; Makris, Ilias; Apostolopoulos, Sotiris; Liargovas, Panagiotis
Abstract : Purpose: The COVID-19 crisis has brought to the forefront the importance of rural health enterprises (RHEs), the peculiarity, in these terms, of rural areas, and the impact of rurality on health entrepreneurial activities. This paper aims to undertake a literature review regarding RHEs in the EU, identify research gaps and set future research directions. Design/methodology/approach: A systematic literature review was conducted and the key aspects coded across four thematic areas – after examining 68 papers. Findings: The findings reveal that more intense research should be conducted across four area which emerged; rural health providers vs urban health providers; RHEs and rural development; RHEs and quality of life; and social RHEs. Research limitations/implications: Future research avenues were identified and suggestions for further research on RHEs were provided. Practical implications: The paper provides insights into how rural areas can attract health enterprises and how health enterprises can operate in rural areas. Originality/value: This research expands on the limited existing knowledge of RHEs and sets the foundations for further research.